Biomimetic Design Concepts in African Textile Prints: Embracing Nature's Influence on Fashion and Textiles - Frederick Boamah; Benjamin Tawiah; Ebenezer Howard (Fashion and Textiles Review)
Purpose: The purpose of this study is to provide a comprehensive review of biomimetic-inspired concepts in surface African printed textiles and fashion products and analyse their cultural and philosophical significance.